2008
DOI: 10.1007/bf03326009
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of hexavalent chromium from aqueous solutions by wheat bran

Abstract: ABSTRACT:In this research, adsorption of chromium (VI) ions on wheat bran has been studied through using batch adsorption techniques. The main objectives of this study are to 1) investigate the chromium adsorption from aqueous solution by wheat bran, 2) study the influence of contact time, pH, adsorbent dose and initial chromium concentration on adsorption process performance and 3) determine appropriate adsorption isotherm and kinetics parameters of chromium (VI) adsorption on wheat bran. The results of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(130 citation statements)
references
References 26 publications
8
117
1
Order By: Relevance
“…Pseudo-first-order, pseudo-second-order, simple Elovich and intra-particle diffusion kinetic models are conventional models examined to investigate the kinetics of adsorption processes (Nameni et al 2008;Mohaptra et al 2009). The pseudo-first-order kinetics model assumes that adsorption is controlled by the diffusion step and its adsorption is proportional to the difference in adsorption capacity at equilibrium and at any time t (q e and q t , respectively, in mg g -1 ).…”
Section: Kinetics Of Adsorptionmentioning
confidence: 99%
“…Pseudo-first-order, pseudo-second-order, simple Elovich and intra-particle diffusion kinetic models are conventional models examined to investigate the kinetics of adsorption processes (Nameni et al 2008;Mohaptra et al 2009). The pseudo-first-order kinetics model assumes that adsorption is controlled by the diffusion step and its adsorption is proportional to the difference in adsorption capacity at equilibrium and at any time t (q e and q t , respectively, in mg g -1 ).…”
Section: Kinetics Of Adsorptionmentioning
confidence: 99%
“…The slope and intercept of the plot of log (q e -q t ) versus t are used to determine the pseudo-firstorder rate constant K ads and q e , respectively. Pseudo-second-order rate equation (Nameni et al 2008) can be expressed in the following form:…”
Section: Resultsmentioning
confidence: 99%
“…[1), which suggests the favorability of multilayered sorption process (Nameni et al 2008). The value of K F was found to be 26.17 L g -1 , which indicated that resin has a high adsorption capacity for Cr(VI) solution.…”
Section: Effect Of Initial Metal Concentration On Removalmentioning
confidence: 99%
“…On the other hand, their structure, phase composition, chemical stability, water insolubility and mechanical strength render them suitable for preparing valuable materials for different uses. Agricultural wastes can be applied as biosorbents, directly or after activation (Sumathi et al 2005;Dias et al 2007;Ioannidou and Zabaniotou 2007;Nameni et al 2008;Garcia-Reyes et al 2009;Gupta et al 2012;Vassileva et al 2013;Yuvaraja et al 2014). The advantages of biosorbents are biodegradability and good adsorption properties due to their morphology and surface functional groups (Ngah and Hanafiah 2008;Ali 2010;Ali et al 2012).…”
Section: Introductionmentioning
confidence: 99%